Partial least squares regression of oil sands processing variables within discrete event simulation digital twin - Wilson, Ryan; Mercier, Patrick H. J; Patarachao, Bussaraporn; Navarra, Alessandro (Minerals (Basel), 2021)
NRC publication: Yes